The corporeal practices of adventure in the context of high school integrated in professional and technological education (Research, Society and Development, 2022)
This article aimed to verify the teachers' understanding of the Corporal Adventure Practices and how they are developed in Physical Education classes in the Integrated High School of the Instituto Federal de Alagoas - IFAL, analyzing their opinion on the importance of approaching this practice. in your classes. For the development of this research, a qualitative approach was used, of the exploratory descriptive type. Data were extracted from semi-structured questionnaires answered by teachers of the curricular component: Physical Education, from seven IFAL campuses. And, submitted to thematic content analysis. From the answers obtained in the semi-structured questionnaire and from the clipping of the recording units with frequent repetitions and the same meaning. After coding, categorization was performed with two common themes: a) The importance of Corporal Adventure Practices in the school environment and possible learning; b) Physical Education teachers facing the challenges of Corporal Adventure Practices at school. The results obtained indicate that despite the difficulties and obstacles that teachers face in the applicability of PCA in their classes, they consider the importance of approaching these practices in the school environment and mention possible learnings, such as overcoming challenges, contact with nature and increase the repertoire with other experiences of the adventure body culture. Thus, it will be able to contribute to the integrated formation of secondary level and the effectiveness of work, science and culture relations in the teaching-learning process of students.